ANALISIS MANAJEMEN BISNIS SYARIAH PENGARUH LITERASI BISNIS DIGITAL TERHADAP CITRA PRODUK PADA APLIKASI SHOPEE PADA MASA COVID 19 (STUDI SAMSUNG OFFICIAL SHOP) - Tulhuda, Basit; Trihantana, Rully; Purnama , Bayu (Sahid Business Journal : Jurnal Penelitian Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2023)
The aim of this research is to analyze and explain whether digital business literacy variables influence or do not influence product image in the Shoppe application during the Covid-19 period. The research method used is a quantitative method with simple linear regression analysis. Data obtained from a questionnaire that was distributed to a total of 349 respondents. The variables in this research are Digital Business Literacy (X) and Product Image (Y). Researchers used SPSS Version 26 tools in the data processing process. The results of this research state that there is a positive and significant influence between digital business literacy and product image, so it can be concluded that the digital business literacy variable (X) influences the product image variable (Y).